Association between sleeping hours and cardiometabolic risk factors for metabolic syndrome in a Saudi Arabian population. Issue 11 (30th November 2015) - Brocato, Jason; Wu, Fen; Chen, Yu; Shamy, Magdy; Alghamdi, Mansour A; Khoder, Mamdouh I; Alkhatim, Alser A; Abdou, Mamdouh H; Costa, Max
Abstract : Objectives: Epidemiological and molecular studies have shown that sleep duration is associated with metabolic syndrome (MtS), a disease that is on the rise in the Kingdom of Saudi Arabia. We aim to investigate the association between sleep duration and selected cardiometabolic risk factors of MtS in a Saudi Arabian population. Setting: Secondary care was given to the participants. There were 2 participating centres, shopping malls in North and South Jeddah, Saudi Arabia. Participants: We recruited 2686 participants over a 1-year study period. Participants were selected based on their willingness. The only criterion for exclusion was living in the area (North or South Jeddah) for less than 15 years. Planned and primary outcome measures: Participants were measured for blood sugar levels, blood pressure and body mass index. All participants were asked to fill out a questionnaire. Results: There was a positive association between longer sleep duration and obesity, hypertension and hyperglycaemia. The adjusted ORs for obesity, hypertension and hyperglycaemia were 1.54 (95% CI 1.20 to 1.98), 1.89 (95% CI 1.45 to 2.48) and 1.59 (95% CI 1.19 to 2.13), respectively, in participants sleeping >8 h/night, as compared with those sleeping 7 h. The positive associations between longer sleep duration, defined as sleeping >7 h, and the disease status, did not differ from other risk factors such as physical activity and nutrition. Conclusions: This is the first epidemiological study reporting on the association between sleep duration and cardiometabolic risk factors of MtS in a Saudi Arabian population. Sleep durations of 8 h or greater were found to be associated with all 3 cardiometabolic risk factors: obesity, hypertension and hyperglycaemia, and this relationship was not confounded by quality of nutrition or physical activity levels.